1997
DOI: 10.1159/000044877
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Calcitriol Improves Anaemia and Reduces the Need for Erythropoietin in Haemodialysis Patients

Abstract: In cases with severe hyperparathyroidism, anaemia improves after parathyroidectomy. The objective of this study was to investigate the influence of treatment with intravenous calcitriol on anaemia in 28 haemodialysis patients. The patients showed moderate to severe hyperparathyroidism (mean parathyroid hormone level 811.6 ± 327 pg/ml) and were treated with calcitriol (2 µg i.v.) after haemodialysis. The follow-up period was 12 months. 21 out of the 28 patients had been receiving erythropoietin (EPO) prior to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
4
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 9 publications
3
60
4
1
Order By: Relevance
“…As for the effect of PTX on hemoglobin levels, beneficial effects have been seen following correction of secondary hyperparathyroidism in chronic renal failure [19, 20, 21]. Ureña et al [19]have reported an increase in circulating erythropoietin levels following PTX in chronic renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…As for the effect of PTX on hemoglobin levels, beneficial effects have been seen following correction of secondary hyperparathyroidism in chronic renal failure [19, 20, 21]. Ureña et al [19]have reported an increase in circulating erythropoietin levels following PTX in chronic renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, intervention with calcitriol improves glucose tolerance 75,76 and lipid parameters, 77 and reduces erythropoietin requirements. 78 In addition to our efforts on cardiac structure and function, ongoing trials are currently testing the role of 1,25(OH) 2 D 3 or a related analog in inflammation (NCT00294866), vascular calcification (NCT00752102), endothelial cell health (NCT00528788), and proteinuria and renal disease (NCT00421733), to name a few.The biology for nutritional replacement of vitamin D also should not be ignored given the magnitude of 25OHD 3 deficiency in chronic renal failure. Recent data on 25OHD 3 and antimicrobial peptides are quite compelling, 79 and this has not gone unnoticed by the nephrology community (e.g., study NCT00749736) given infection is the second most common cause of mortality in chronic renal failure.…”
mentioning
confidence: 99%
“…For example, intervention with calcitriol improves glucose tolerance 75,76 and lipid parameters, 77 and reduces erythropoietin requirements. 78 In addition to our efforts on cardiac structure and function, ongoing trials are currently testing the role of 1,25(OH) 2 D 3 or a related analog in inflammation (NCT00294866), vascular calcification (NCT00752102), endothelial cell health (NCT00528788), and proteinuria and renal disease (NCT00421733), to name a few.…”
mentioning
confidence: 99%
“…Appropriate iron stores seem to be protective [76] because aluminum and iron share common pathways for intestinal absorption, serum transport and cellular uptake. Vice versa, aluminum overload may be one reason for iron-resistant anemia and resistance to erythropoietin [77] which might be overcome by intravenous calcitriol [78]. …”
Section: The Many Faces Of Renal Osteodystrophymentioning
confidence: 99%